2021
DOI: 10.1155/2021/5512708
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Fracture Resistance of Restored Premolars with Novel Composite Materials: An In Vitro Study

Abstract: During restorative treatment, premolars restored with resin filling materials using the conventional incremental-fill technique take longer restoration time and undermine the integrity of the tooth. The aim of this study was to assess fracture resistance of premolars restored by various types of novel bulk-fill composite resin materials. Forty-eight (n = 48) freshly extracted sound maxillary first premolars were used in this in vitro study. The teeth were divided into six groups, each having 8 specimens. Group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 40 publications
1
1
0
Order By: Relevance
“…Previous research [33] has confirmed that intact teeth have higher fracture resistance than root canaltreated teeth with different core materials. The fracture resistance of the control group was measured to be 1203.66 ± 54.06 N, which is similar to the results reported by Al-Ibraheemi ZA et al [34] and Kaur B et al [35]. The decrease in strength can be attributed to the uneven distribution of stress caused by the endodontic post, which does not effectively balance the load along weakened root walls due to root canal preparation [36].…”
Section: Discussionsupporting
confidence: 83%
“…Previous research [33] has confirmed that intact teeth have higher fracture resistance than root canaltreated teeth with different core materials. The fracture resistance of the control group was measured to be 1203.66 ± 54.06 N, which is similar to the results reported by Al-Ibraheemi ZA et al [34] and Kaur B et al [35]. The decrease in strength can be attributed to the uneven distribution of stress caused by the endodontic post, which does not effectively balance the load along weakened root walls due to root canal preparation [36].…”
Section: Discussionsupporting
confidence: 83%
“…As resinas Filtek (Z350 -3M) apresentam em sua composição o Bisfenol A diglicidil éter dimetacrilato (BisGMA), e assim como os outros materiais os quatro componentes estruturais básicos são: uma matriz polimérica, partículas de carga inorgânica (geralmente vidros de sílica radiopacos), silano e promotores/reguladores da reação de polimerização (Ferracane., 2011), dessa forma justificando a sua alta utilização principalmente em dentes posteriores pois são capazes de resistir à fratura ao receber uma grande quantidade de pressão oclusal (Al-Ibraheemi et al, 2021).…”
Section: Discussionunclassified
“…However, Ilie et al suggested reduced light scattering at the filler/matrix interface of BBR and reported some enhanced micro-mechanical properties relative to conventional RBCs [21]. BBR restorations have also been reported to have greater fracture resistance, possibly due to high filler load and elastic modulus [47]. Within OBF, addition-fragmentation monomers may produce more homogeneous network structures to resist fracture stress [14,48].…”
Section: Discussionmentioning
confidence: 99%